Crop photosynthetic capacity of grain sorghum (Sorghum bicolor (L.) Moench) depending on sowing time and planting depth - Л. А. Правдива (Plant Varieties Studying and Protection)
Purpose. To establish the optimal seeding time and depth of ‘Dniprovskyi 39’ and ‘Vinets’ sorghum varieties, to prove their effect on the crop photosynthetic capacity in the Right-Bank Forest-Steppe of Ukraine. Methods. Field, laboratory, comparative, analytical, generalizing, mathematical and statistical. Results. It was proved that the best results of crop photosynthetic capacity of sorghum were obtained by sowing in the first decade of May (the second sowing period) at a seeding depth of 4–6 cm. Accordingly, the leaf surface area in these variants reached its maximum during the “panicle-blooming” period and equated 36.13–38.81 thousand m2/ha for the ‘Dniprovskyi 39’ variety and 34.23–36.91 thousand m2/ha for the ‘Vinets’ variety. By sowing seeds in the third decade of April (the first sowing period) at the seedining depth values described above the leaf surface area of the varieties was slightly smaller and amounted to 29.56–31.20 thousand m2/ha for the ‘Dniprovskyi 39’ variety and 27.76–29.40 thousand m2/ha for the ‘Vinets’ variety. By sowing seeds in the second decade of May (the third sowing period), the leaf surface area was 30.68–32.92 thousand m2/ha for the ‘Dniprovskyi 39’ variety and 29.08–31.32 thousand m2/ha for the ‘Vinets’ variety. The highest photosynthetic potential was obtained for sorghum plants in the second sowing period at the seeding depth of 4–6 cm and was 1.27 and 1.34 million m2/ha for the ‘Dniprovskyi 39’ variety and 1.16 and 1.22 million m2/ha for the variety ‘Vinets’. In the first sowing period, this indicator was slightly lower and amounted to 1.18 and 1.23 million m2/ha for the ‘Dniprovskyi 39’ variety and 0.98 and 1.02 million m2/ha for the ‘Vinets’ variety respectively. In the third sowing period, it was the smallest one and equated 1.09 and 1.13 million m2/ha for the ‘Dniprovskyi 39’ variety, and 0.88 and 0.93 million m2/ha for the ‘Vinets’ variety at the optimal seeding depth. The photosynthetic potential was lower at the seeding depth of 2 and 8 cm, which is explained by the different soil and climatic parameters during a certain period of sorghum plant vegetation. The highest value of the photosynthetic capacity net indicator was obtained by sowing seeds at the optimal time and the optimal seeding depth and it equated 3.84–4.02 g/m2 per day for the ‘Dniprovskyi 39’ variety and 3.79 – 3.98 g/m2 per day for the ‘Vinets’ variety. Conclusions. It has been established that the sorghum plants had better vegetation and formed photosynthetic capacity by sowing seeds in the first decade of May at the planting depth of 4–6 cm, which we recommend for growing this crop in the Right-Bank Forest-Steppe of Ukraine.